Filamentous Phage Active on the Gram-Positive Bacterium Propionibacterium freudenreichii - Chopin, Marie-Christine (American Society for Microbiology, 2002)
We present the first description of a single-stranded DNA filamentous phage able to replicate in a gram-positive bacterium. Phage B5 infects Propionibacterium freudenreichii and has a genome consisting of 5,806 bases coding for 10 putative open reading frames. The organization of the genome is very similar to the organization of the genomes of filamentous phages active on gram-negative bacteria. The putative coat protein exhibits homology with the coat proteins of phages PH75 and Pf3 active on Thermus thermophilus and Pseudomonas aeruginosa, respectively. B5 is, therefore, evolutionarily related to the filamentous phages active on gram-negative bacteria.